Bone-specific alkaline phosphatase – a potential biomarker for skeletal growth assessment. (2nd January 2018) - Tripathi, Tulika; Gupta, Prateek; Sharma, Jitender; Rai, Priyank; Gupta, Vinod Kumar; Singh, Navneet
ABSTRACT: Objective : The present study was aimed to assess levels of serum Bone-specific alkaline phosphatase (BALP) and serum Insulin-like growth factor-1 (IGF-1) and comparing with cervical vertebral maturation index (CVMI) stages. Design : Cross-sectional study. Setting : Maulana Azad Institute of Dental Sciences, New Delhi, India. Participants : 150 subjects (75 males and 75 females) in the age group of 8–20 years. Methods : Subjects were divided into six CVMI stages. Enzyme-linked immunosorbant assay was performed for the estimation of serum BALP and serum IGF-1 levels. Mann–Whitney U test was performed to compare mean ranks of serum BALP and serum IGF-1 with different CVMI stages. Spearman correlation between serum BALP and serum IGF-1 was done across 6 CVMI stages. Results : Peak serum IGF-1 levels were found at CVMI stages 4 and 3 for males and females respectively. Peak levels for serum BALP were found at stage 3 for both genders with significant differences from other stages. A statistically significant correlation was seen between serum IGF-1 and serum BALP from CVMI stages 1 to 3 and 4 to 6 ( p < .01). Conclusions : BALP showed promising results and can be employed as a potential biomarker for the estimation of growth status.